The Contribution of Three-Dimensional Power Doppler Imaging in the Preoperative Assessment of Breast Tumors: A Preliminary Report. (16th June 2009) - Kalmantis, K.; Dimitrakakis, C.; Koumpis, Ch.; Tsigginou, A.; Papantoniou, N.; Mesogitis, S.; Antsaklis, A.
Abstract : Purpose . The aim of this study was to determine the value of 3D and 3D Power Doppler sonography in the detection of tumor malignancy in breast lesions and to find new diagnostic criteria for differential diagnosis. Methods . One hundred and twenty five women with clinically or mammographically suspicious findings were referred for 3D Power Doppler ultrasound prior to surgery. Histological diagnosis was conducted after surgery and compared with ultrasound findings. Sonographic criteria used for breast cancer diagnosis were based on a system that included morphological characteristics and criteria of the vascular pattern of a breast mass by Power Doppler imaging. Results . Seventy-two lesions were histopathologically diagnosed as benign and 53 tumors as malignant. Three-dimensional ultrasound identified 49 out of 53 histologically confirmed breast cancers resulting in a sensitivity of 92.4% and a specificity of 86.1% in diagnosing breast malignancy (PPV: 0.83, NPV:0.94). Conclusions . 3D ultrasonography is a valuable tool in identifying preoperatively the possibility of a tumor to be malignant.